2015
DOI: 10.1016/j.neuint.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Lack of presynaptic interaction between glucocorticoid and CB1 cannabinoid receptors in GABA- and glutamatergic terminals in the frontal cortex of laboratory rodents

Abstract: Corticosteroid and endocannabinoid actions converge on prefrontocortical circuits associated with neuropsychiatric illnesses. Corticosteroids can also modulate forebrain synapses by using endocannabinoid effector systems. Here, we determined whether corticosteroids can modulate transmitter release directly in the frontal cortex and, in doing so, whether they affect presynaptic CB1 cannabinoid receptor- (CB1R) mediated neuromodulation. By Western blotting of purified subcellular fractions of the rat frontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
4
1
Order By: Relevance
“…Notwithstanding, a recent characterization of O-2050 revealed some unexpected in vitro partial agonist activity in cyclic AMP assay, and a lack of antagonism on in vivo effects of Δ 9 -THC and WIN55212-2 [393]. In our hands, O-2050 (1 µM) had no effect on the depolarizationinduced release of GABA, glutamate and serotonin in the frontal cortex [396,397], and prevented the inhibitory action of WIN55212-2. In that sense, it mimicked the effect of the genetic deletion of the CB 1 R and we concluded that O-2050 is a useful in vitro CB 1 R antagonist up to the concentration of 1 µM.…”
Section: Multifaceted Interaction Of Ligands and G Proteins With The contrasting
confidence: 47%
See 1 more Smart Citation
“…Notwithstanding, a recent characterization of O-2050 revealed some unexpected in vitro partial agonist activity in cyclic AMP assay, and a lack of antagonism on in vivo effects of Δ 9 -THC and WIN55212-2 [393]. In our hands, O-2050 (1 µM) had no effect on the depolarizationinduced release of GABA, glutamate and serotonin in the frontal cortex [396,397], and prevented the inhibitory action of WIN55212-2. In that sense, it mimicked the effect of the genetic deletion of the CB 1 R and we concluded that O-2050 is a useful in vitro CB 1 R antagonist up to the concentration of 1 µM.…”
Section: Multifaceted Interaction Of Ligands and G Proteins With The contrasting
confidence: 47%
“…Steroid hormones interact with the endocannabinoid system, which has significant therapeutic potential. One important feature of glucocorticoid receptors (GcRs) is that they co-localize with DAGLα in post-synaptic neural compartments apposing CB 1 R-positive nerve terminals in the brain [397]. GcR activation in the prefrontal cortex triggers endocannabinoid release [966], which in turn downregulates the hypothalamo-pituitary-adrenal (HPA) axis to decrease circulating corticosteroid levels [967,968], facilitate the extinction and impair the retrieval of aversive memories [965,967,[969][970][971].…”
Section: δ 9 -Thc and Steroid Hormonesmentioning
confidence: 99%
“…2). Like in the hypothalamus, recent data indicate that the GR in the frontal cortex are expressed on postsynaptic profiles (3). Excitatory projections from these brain regions accelerate the poststress decline in circulating glucocorticoids likely through activation of inhibitory inputs from the bed nucleus of the stria terminalis to the PVN (31, 35).…”
Section: Glucocorticoids Affect Synaptic Plasticity Via Endogenous Cbmentioning
confidence: 99%
“…Neuromodulators enhance the flexibility of neural networks by multiple mechanisms. These include the regulation of intrinsic properties (i.e., pre-existing conductances; Benson and Levitan, 1983 ; Kiehn and Harris-Warrick, 1992a , b ; Harris-Warrick et al, 1995 ; Galbavy et al, 2013 ), modulating synaptic properties ( Johnson et al, 1993a , b,1995 ; Zhao et al, 2011 ; Bitencourt et al, 2015 ; Böhm et al, 2015 ), reconfiguring participating neurons within the network ( Hooper and Moulins, 1989 ; Fénelon et al, 1998 ; Lieske et al, 2000 ), and modulating plasticity and even modulation itself ( Mesce, 2002 ; McLean and Sillar, 2004 ; Zhou et al, 2007 ; Pawlak et al, 2010 ; Lawrence et al, 2015 ). Another important mechanism of the regulation of neuronal excitability is the modulation of leak currents ( Bayliss et al, 1992 ; Erxleben et al, 1995 ; Talley et al, 2000 ; Cymbalyuk et al, 2002 ; Xu et al, 2009 ), and of the ratio of leak current to pacemaking current amplitude (and not just the pacemaking current amplitude), as is the case in the regulation of pacemaking activity in the pre-Bötzinger complex ( Del Negro et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%